Congenital and developmental cataract surgery with undercorrected Intraocular lens (IOL) power implantation targeting emmetropia at 8 years of age and post-operative refractive status - Bajracharya, Kabindra; Hirachan, Anjita; Joshi, Kriti; Bajracharya, Bimala (Asian Journal of Medical Sciences, 2021)
Background: In congenital and developmental cataract primary undercorrection of intraocular lens (IOL) power is a common practice. However, long-term refractive status of these children is largely unknown. Aims and Objective: To analyse refractive status after cataract surgery with undercorrected IOL power implantation in congenital and developmental cataract. Materials and Methods: This study was descriptive, retrospective conducted for three years from 1st January 2013 to 31st December 2015. The children (> 6 months to <=7 years of age) who underwent cataract surgery for congenital and developmental cataract with a primary IOL implantation and had reached the age of 8 years were studied. The data were collected in terms of demography, axial length, biometry, IOL implanted, hyperopic correction and postoperative refractive status at 8 years. Results: Total numbers of children operated were 181 with total eyes 288. Unilateral cases were 74 (40.88%) and bilateral 107 (59.12%). Male were 121 (66.85%) and female were 60 (33.15%) with male is to female ratio of 2:1. Right eye was involved in 152 (52.8%) and left eye 136 (47.2%). The mean axial length at the age of one year was 20.75 mm, and gradually increased as age increased which was 22.47 mm at 6 years. The mean biometry was 27.9 diopter (D) at the age of one year which gradually decreased as age increased. Of the total 288 congenital cataract operated, complete follow-up documents were available for 77 (26.74%) eyes up to 8 years which showed emmetropia achieved in 25.97%, myopia in 28.57% and hypermetropia in 45.45%. Conclusion: Primary IOL implantation with hyperopic correction is accepted practice in congenital and developmental cataract. Emmetropia can be achieved however some hyperopic or myopic refractive status at the age of 8 years is not a surprise. Myopic shift continues as the age increases. Parent awareness for early detection and surgery, optical correction and regular follow-up are essential for good outcome.